Dark Triad traits, alexithymia, and emotion regulation as predictors of depression, anxiety, and stress in clinical and non-clinical samples - Hornstein, Leah; Schleicher, Daniel; Ecker, Angelika; Kandsperger, Stephanie; Brunner, Romuald; Jarvers, Irina (Frontiers in Psychology, 2025)
IntroductionEmotion regulation and personality traits critically influence mental health. Dark Triad characteristics—Machiavellianism, psychopathy, and narcissism—are linked to distress and maladaptive coping, yet their specific associations with depression, anxiety, and stress remain unclear. This study examined how Dark Triad traits, alexithymia facets, and emotion regulation strategies relate to psychopathological symptoms in a German sample.MethodsA cross-sectional online survey was completed by 425 adults (72.2% female, 1.4% diverse, M = 31.36, SD = 12.21 range 18–73 years) recruited from the general population and inpatient and outpatient psychiatric clinics in Regensburg, Germany. Participants completed the Naughty Nine questionnaire as well as the Perth Alexithymia Questionnaire (PAQ), the Emotion Regulation Questionnaire (ERQ), and the Depression Anxiety Stress Scale (DASS-21). Analyses included Kendall’s tau-b correlations, multiple regression with robust standard errors, Kruskal-Wallis tests, and post-hoc comparisons.ResultsMachiavellianism was correlated with depression (p = 0.023), anxiety (p = 0.018) and perceived stress (p < 0.001) and remained an predictor of both anxiety (β = 0.13, p = 0.013 and perceived stress (β = 0.13, p = 0.010), even when controlling for alexithymia and emotion regulation. Psychopathy showed positive bivariate associations with depression and expressive suppression but did not predict distress in the multivariate models. Narcissism was modestly correlated with depression, anxiety, and stress (all p < 0.05), and emerged as a predictor of perceived stress only (β = 0.10, p = 0.042). The alexithymia facet difficulty appraising positive feelings (PDAF) contributed additional explained variance in psychopathology beyond Dark Triad traits and emotion regulation (ΔR2 range: 0.07–0.09, all p < 0.01). No significant differences in Dark Triad scores were found across treatment-status groups.DiscussionMachiavellianism was uniquely associated with higher anxiety and stress, and narcissism with greater perceived stress, psychopathy showed no unique links. Difficulties appraising positive affect (PDAF) accounted for additional variance in all measures of psychopathology. These associations suggest that anxiety-management strategies may suit those high in Machiavellianism, stress-reduction approaches those high in narcissism, and positive-affect training could benefit all by targeting PDAF. Longitudinal studies should confirm these links and evaluate combined trait- and emotion-based interventions.